Associations of paediatric demyelinating and encephalitic syndromes with myelin oligodendrocyte glycoprotein antibodies: a multicentre observational study. Issue 3 (March 2020) - Armangue, Thaís; Olivé-Cirera, Gemma; Martínez-Hernandez, Eugenia; Sepulveda, Maria; Ruiz-Garcia, Raquel; Muñoz-Batista, Marta; Ariño, Helena; González-Álvarez, Veronica; Felipe-Rucián, Ana; Jesús Martínez-González, Maria; Cantarín-Extremera, Veronica; Concepción Miranda-Herrero, Maria; et al.
Summary: Background: Investigations of myelin oligodendrocyte glycoprotein (MOG) antibodies are usually focused on demyelinating syndromes, but the entire spectrum of MOG antibody-associated syndromes in children is unknown. In this study, we aimed to determine the frequency and distribution of paediatric demyelinating and encephalitic syndromes with MOG antibodies, their response to treatment, and the phenotypes associated with poor prognosis. Methods: In this prospective observational study, children with demyelinating syndromes and with encephalitis other than acute disseminated encephalomyelitis (ADEM) recruited from 40 secondary and tertiary centres in Spain were investigated for MOG antibodies. All MOG antibody-positive cases were included in our study, which assessed syndromes, treatment and response to treatment (ie, number of relapses), outcomes (measured with the modified Rankin scale [mRS]), and phenotypes associated with poor prognosis. We used Fisher's exact and Wilcoxon rank sum tests to analyse clinical features, and survival Cox regression to analyse time to antibody negativity. Findings: Between June 1, 2013, and Dec 31, 2018, 239 children with demyelinating syndromes (cohort A) and 296 with encephalitis other than ADEM (cohort B) were recruited. 116 patients had MOG antibodies, including 94 (39%) from cohort A and 22 (7%) from cohort B; 57 (49%) were female, with a median age of 6·2 years (IQR 3·7–10·0). Presenting syndromes in these 116 patients included ADEM (46 [68%]), encephalitis other than ADEM (22 [19%]), optic neuritis (20 [17%]), myelitis (13 [11%]), neuromyelitis optica spectrum disorders (six [5%]), and other disorders (nine [8%]). Among the patients with autoimmune encephalitis in cohort B (n=64), MOG antibodies were more common than all neuronal antibodies combined (22 [34%] vs 21 [33%]). After a median follow-up of 42 months (IQR 22–67), 33 (28%) of the 116 patients had relapses, including 17 (17%) of 100 diagnosed at first episode. Steroids, intravenous immunoglobulin, or plasma exchange were used in 100 (86%) patients at diagnosis, and 32 (97%) of 33 at relapses. Rituximab was mainly used at relapses (11 [33%]). 99 (85%) of 116 patients had substantial recovery (mRS <2) and 17 (15%) moderate to severe deficits (mRS >2; one died). Phenotypes of poor prognosis included ADEM-like relapses progressing to leukodystrophy-like features, and extensive cortical encephalitis evolving to atrophy. Time to antibody negativity was longer in patients with relapses (HR 0·18, 95% CI 0·05–0·59). Interpretation: The spectrum of paediatric MOG antibody-associated syndromes is wider than previously reported and includes demyelinating syndromes and encephalitis. Recognition of these disorders has important clinical and prognostic implications. Funding: Mutua Madrileña Foundation; ISCIII–Subdirección General de Evaluación y Fomento de la Investigación Sanitaria; Fondo Europeo de Desarrollo Regional; Pediatrics Spanish Society; Departament de Salut, Generalitat de Catalunya; Marato TV3 Foundation; Red Española de Esclerosis Múltiple; La Caixa Foundation; and Fundació CELLEX.